FACTORS INFLUENCING PERCEPTION OF UNIVERSITY STUDENTS TOWARDS INTERNET RECRUITMENT - Wendy Ming-Yen Teoh,; Sy-Cha Tan,; Siong Choy Chong, (Asian Academy of Management Journal, 2013)
This study aims to determine the factors influencing perception of university students towards Internet recruitment. Data was collected from 250 university students from five universities based on self-reporting questionnaires e-mailed to them. The results indicate that factors such as user friendliness, information provision, and website usability have significant relationships with the perception of university students towards Internet recruitment. Amongst the three factors, information provision appears to be the strongest predictor. It can be concluded that Internet recruitment will continue to gain prominence and employers must pay considerable attention to their online recruitment information, appearance, features, and functions if they wish to attract the right job candidates.